By: |
![]() THEN ((h(x ![]() ![]() ![]() ((& h(x) = g(x)+g(x ![]() ![]() ![]() ((& h(y) = g(y)+g(x ![]() ![]() ![]() ((& ( ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ((& By (Rewrite by h = split_factor2(g; x; y) ![]() ![]() ![]() ![]() ![]() ![]() ((& By (THEN ((& By (Def of split_factor2(g; x; y) ((& By (THEN ((& By (Reduce Concl ... ![]() ![]() (THEN (Auto ![]() |
1 |
![]() ![]() ![]() ![]() 10. h = split_factor2(g; x; y) 11. h(x ![]() ![]() ![]() 12. h(x) = g(x)+g(x ![]() ![]() ![]() 13. h(y) = g(y)+g(x ![]() ![]() ![]() 14. ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() ![]() | PREMISE |
About:
![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() | ![]() |